Assessment of the feed additive consisting of a strain belonging to Eggerthellaceae family (DSM 11798) for pigs and all avian species (1m01) for the renewal of its authorisation (BIOMIN GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for renewal of the authorisation of the preparation containing viable cells of the bacterium DSM 11798 intended for use as a technological additive (functional group: substances for reduction of the contamination of feed by mycotoxins) in feed for pigs and all avian species. The applicant provided evidence that the additive currently on the market complies with the existing terms of the authorisation. The identification of the active agent has been changed and it belongs to the Eggerthellaceae family. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the additive remains safe for piglets, pigs for fattening and all avian species, consumers and the environment under the approved terms of the authorisation. Regarding user safety, the additive is not a skin or eye irritant. However, it should be considered a skin and respiratory sensitiser, and any exposure through the skin and respiratory tract is a risk. This conclusion would apply, in principle, to any preparation containing the active agent. There is no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.